Electrochemistry of Layered Semiconducting AIIIBVI Chalcogenides: Indium Monochalcogenides (InS, InSe, InTe). Issue 11 (6th May 2019) - Wang, Yong; Szökölová, Katerina; Nasir, Muhammad Zafir Mohamad; Sofer, Zdenek; Pumera, Martin
Abstract: Layered A III B VI chalcogenides represent an interesting class semiconductors, where most of adopting 2D structures. Unlike the typical sandwiched structure of transition metal dichalcogenides (TMDs), layered A III B VI chalcogenides like InSe and GaSe are composed of X−M−M−X motif where M is gallium/indium and X is sulfur/selenium/tellurium. The exception is InS, which adopt an orthorhombic 3D structure. Herein, we studied and compared the inherent electrochemical properties as well as the electrocatalytic performances towards hydrogen evolution (HER), oxygen evolution (OER) and oxygen reduction reaction (ORR) of indium monochalcogenides (InS, InSe and InTe). Inherent electrochemistry studies in phosphate buffered saline electrolyte showed that InS did not exhibit any inherent electrochemical signals when compared to bare glassy carbon electrode. However, InSe showed a reduction peak at −1.6 V while InTe had an oxidation peak at 0.2 V. The heterogeneous electron transfer (HET) rates of indium monochalcogenides were measured with [Fe(CN)6 ] 3−/4− redox probe using cyclic voltammetry ( vs . Ag/AgCl) at the scan rate of 100 mV s −1 . It was found that InTe exhibited the best electrochemical performance with the fastest HET rate with highest k o b s 0 obtained (3.7×10 −3  cm s −1 ). InS showed the best electrocatalytic performance for HER with the lowest overpotential value of 0.92 V at current density of −10 mA cm −2 . However, the performances of indium monochalcogenides were almost comparable to that of bare glassy carbon electrode and do not exhibit any improvements in electrocatalytic capabilities. This study provides insights into the electrochemical properties and electrocatalytic performances of layered A III B VI indium monochalcogenides which would influence potential applications. Abstract : Hot property ! We studied and compared the inherent electrochemical properties as well as the electrocatalytic performances towards hydrogen evolution, oxygen evolution and oxygen reduction reaction of indium monochalcogenides (InS, InSe and InTe).